pFOE or pFTOE as an Early Marker for Impaired Peripheral Microcirculation in Neonates - Nina Hoeller; Christina H. Wolfsberger; Daniel Pfurtscheller; Corinna Binder-Heschl; Bernhard Schwaberger; Berndt Urlesberger; Gerhard Pichler (MDPI AG, 2022)
Background: Peripheral-muscle-fractional-oxygen-extraction (pFOE) and peripheral-muscle-fractional-tissue-oxygen-extraction (pFTOE) are often equated, since both parameters are measured with near-infrared-spectroscopy (NIRS) and estimate oxygen extraction in the tissue. The aim was to investigate the comparability of both parameters and their potential regarding detection of impaired microcirculation. Methods: Term and preterm neonates with NIRS measurements of upper (UE) and lower extremities (LE) were included. pFOE was calculated out of peripheral-muscle-mixed-venous-saturation (pSvO2), measured with NIRS and venous occlusion, and arterial oxygen saturation (SpO2). pFTOE was calculated out of peripheral-muscle-tissue-oxygen-saturation and SpO2. Both parameters were compared using Wilcoxon-Signed-Rank-test and Bland-Altman plots. Results: 341 NIRS measurements were included. pFOE was significantly higher than pFTOE in both locations. Bland-Altman plots revealed limited comparability, especially with increasing oxygen extraction with higher values of pFOE compared to pFTOE. Conclusion: The higher pFOE compared to pFTOE suggests a higher potential of pFOE to detect impaired microcirculation, especially when oxygen extraction is elevated.